2018
DOI: 10.1111/jdv.14805
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell papulosis associated with B‐cell malignancy: a distinctive clinicopathologic entity

Abstract: We propose the denomination 'T-cell papulosis associated with B-cell malignancy' (TCP-BCM) for this distinctive eruption. Although resulting in various histopathological pictures, it can be easily recognized by clinicians and may be identified by informed pathologists relying on some key features. An extravasation of tumour B cells with skin-homing properties associated with a secondary, predominant, T-cell immune reaction could explain the clinicopathologic aspect and the prolonged regressive and recurrent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 30 publications
7
40
3
Order By: Relevance
“…In light of our results and other recent findings, the definition of ED as a nonspecific reaction pattern must be questioned. Mitteldorf et al were the first who identified CLL‐cells in skin specimens of an ED patient using IgH‐PCR and FISH analysis and speculated on a pathogenic role of leukemic cells in ED.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…In light of our results and other recent findings, the definition of ED as a nonspecific reaction pattern must be questioned. Mitteldorf et al were the first who identified CLL‐cells in skin specimens of an ED patient using IgH‐PCR and FISH analysis and speculated on a pathogenic role of leukemic cells in ED.…”
Section: Discussioncontrasting
confidence: 53%
“…As observed in our cases, diagnosis of underlying hematologic disease usually precedes the onset of ED and accurate diagnosis of ED is commonly delayed by months resulting in impaired quality of life . Recently, Visseaux et al have proposed a new denomination of ED as “T‐cell papulosis associated with B‐cell malignancy” (TCB‐BCM). This term eliminates the reference to eosinophilic infiltration as a hallmark of the diagnostic criteria established by Byrd et al Interestingly, the authors included about 25% of patients where eosinophils were absent and thus diagnosis of ED would have been missed by the established histological diagnostic criteria .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations